Harvard Business Review project management handbook : how to launch, lead, and sponsor successful projects - Nieto-Rodriguez, Antonio (Boston, MA : Harvard Business Review Press, 2021)
"The one primer you need to launch, lead, and sponsor successful projects. We're now living in the project economy. As the number of projects initiated in both the public and private sectors skyrockets, project management skills have become essential for all leaders and managers. But despite this project boom, the failure rate remains extremely high. Why? Leaders have too many projects and too little visibility into them, and they lack the project implementation competencies necessary to deliver their projects successfully. Project managers have the technical skills, but they often have trouble translating their hands-on know-how up to the leaders'-eye view. Worthy projects languish and fail to deliver benefits, starved of resources, while too much investment is made in projects with less merit or potential value. The HBR Project Management Handbook will help you bridge this gap. In this comprehensive guide, project management expert Antonio Nieto-Rodriguez presents a simple and intuitive framework that will increase any project's likelihood of success. Packed with case studies from many industries worldwide, you'll learn to more effectively navigate through your organization's inventory of projects, programs, and strategic, and agile initiatives in order to better select which ones to push forward and which to kill, as well as how they should be prioritized and how you can ensure they're completed as planned. Timeless yet forward-looking, the advice in this book will help you and your organization thrive in the project-driven world. HBR Handbooks provide ambitious professionals with the frameworks, advice, and tools they need to excel in their careers. With step-by-step guidance, time-honed best practices, real-life stories, and concise explanations of research published in Harvard Business Review, each comprehensive volume helps you to stand out from the pack-whatever your role"--
Introduction: Welcome to the project economy -- Part 1. Project fundamentals for everybody: Projects everywhere -- from a world driven by efficiency to a world driven by change -- What is a project? -- from product launches to digital transformation to megaprojects -- What project management is now -- and why it needed to be reinvented -- Part 2. The project canvas: Introduction to the project canvas -- one tool for any project-traditional, agile, or hybrid -- The foundation -- purpose, investment, benefits -- The people -- sponsorship, resources, stakeholders -- The creation -- deliverables, plan, change -- Putting the project canvas into practice -- adopting the canvas in your organization -- Part 3. Individual and organizational project competencies: Project leadership -- competencies for effective project management and sponsorship -- Selecting and prioritizing projects -- managing your project portfolio -- The agile and project-driven organization -- building the structure and culture needed for project success -- Part 4. A better future through projects: Project managing a better future -- tomorrow's innovations and disruptions in project management.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Project management -- Handbooks, manuals, etc; Project management; elektronické knihy; electronic books